Characterization of the ammonification, the relevant protease production and activity in a high-efficiency ammonifier Bacillus amyloliquefaciens DT. (August 2019) - Hui, Cai; Wei, Ran; Jiang, Hui; Zhao, Yuhua; Xu, Ligen
Abstract: High-efficiency ammonifiers are imperative for the treatment of wastewater with high organic nitrogen content. Ammonification characteristics and the corresponding protease production and activity of a Bacillus amyloliquefaciens was studied using simulated wastewater. High ammonification was observed with more than 500 mg/L NH4 + released from tryptone medium after 18-h cultivation and almost all the organic nitrogen was transformed to NH4 + -N and biomass. Single factor experiments were performed to optimize the conditions. For ammonification, pH 5, 25–37 °C, and a C:N ratio <15 were optimal; for protease production, pH 7, 30 °C and addition of 2 mM Mn 2+ were favorable, whereas pH 8, 50–60 °C and the presence of 1 mM Mn 2+ showed the highest protease activity. Moreover, protease inhibition experiment indicated that Bacillus amyloliquefaciens DT simultaneously produces metalloprotease and serine protease. Correlation analysis indicated that protease production and ammonification were tightly coupled with cell growth during the logarithmic growth phase. However, temperature had different influence on the correlations between protease secretion and cell growth. These findings are expected to help in designing a high-efficiency reactor for the treatment of wastewater with high organic nitrogen and enhance our understanding of the production and activity of proteases during the ammonification process. Highlights: Ammonification and the related protease of a Bacillus amyloliquefaciens was studied. Bacillus amyloliquefaciens DT showed high ammonification. The ammonification of strain DT was coupled tightly with cell growth. The protease mainly produced during the logarithmic growth phase. Bacillus amyloliquefaciens DT could produce metalloprotease and serine protease.